2016
DOI: 10.1161/circep.115.003151
|View full text |Cite
|
Sign up to set email alerts
|

Multielectrode Pulmonary Vein Isolation Versus Single Tip Wide Area Catheter Ablation for Paroxysmal Atrial Fibrillation

Abstract: Background— Single-shot ablation techniques may facilitate safe and simple pulmonary vein isolation to treat paroxysmal atrial fibrillation. Multielectrode pulmonary vein isolation versus single tip wide area catheter ablation-paroxysmal atrial fibrillation is the first multinational, multicenter, prospective, noninferiority randomized clinical trial comparing multielectrode-phased radiofrequency ablation (MEA) to standard focal irrigated radiofrequency ablation (STA) using 3-dimensional navigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“… 731 , 732 This ablation system was not approved for clinical use by the FDA due in part to this initial safety signal and the occurrence of 4 strokes (2.9% of patients randomized to ablation) following ablation in the pivotal Tailored Treatment of Permanent Atrial Fibrillation study. 733 , 734 An additional single-arm study to again elucidate the safety of PVAC technology, the Evaluation of Multielectrode Phased RF Technology in Persistent AF (NCT01693120), was subsequently launched but has recently been closed due to lack of enrollment. In summary, there is considerable reason and data to believe that PVAC technology in its redesigned format has achieved at least a similar safety profile as CB or irrigated tip catheter ablation.…”
Section: Section 6: Technology and Toolsmentioning
confidence: 99%
“… 731 , 732 This ablation system was not approved for clinical use by the FDA due in part to this initial safety signal and the occurrence of 4 strokes (2.9% of patients randomized to ablation) following ablation in the pivotal Tailored Treatment of Permanent Atrial Fibrillation study. 733 , 734 An additional single-arm study to again elucidate the safety of PVAC technology, the Evaluation of Multielectrode Phased RF Technology in Persistent AF (NCT01693120), was subsequently launched but has recently been closed due to lack of enrollment. In summary, there is considerable reason and data to believe that PVAC technology in its redesigned format has achieved at least a similar safety profile as CB or irrigated tip catheter ablation.…”
Section: Section 6: Technology and Toolsmentioning
confidence: 99%
“… 731 , 732 This ablation system was not approved for clinical use by the FDA due in part to this initial safety signal and the occurrence of 4 strokes (2.9% of patients randomized to ablation) following ablation in the pivotal Tailored Treatment of Permanent Atrial Fibrillation study. 733 , 734 An additional single-arm study to again elucidate the safety of PVAC technology, the Evaluation of Multi-electrode Phased RF Technology in Persistent AF (NCT01693120), was subsequently launched but has recently been closed due to lack of enrollment. In summary, there is considerable reason and data to believe that PVAC technology in its redesigned format has achieved at least a similar safety profile as CB or irrigated tip catheter ablation.…”
Section: Section 6: Technology and Toolsmentioning
confidence: 99%
“…The results of the prospective, randomized Multielectrode Pulmonary Vein Isolation Versus Single Tip Wide Area Catheter Ablation (MYSTIC) trial are reported in this edition, 5 which compared standard, irrigated tip radiofrequency ablation with multielectrode-phased radiofrequency ablation (PVAC). As per the reports from 4 experienced centers in the Netherlands and Belgium, rates of single-procedure acute success rates were identical and without any serious adverse events in the first 30 days.…”
Section: See Article By Boersma Et Almentioning
confidence: 99%